Production of mung bean protein isolates by isoelectric precipitation and ultrafiltration-diafiltration: impact on the composition, structural and techno-functional properties as well as in vitro digestibility - Florence Dubois-Laurin; Ugo Berthelot; Alexia Gravel; Véronique Perreault; Haïrati Aboubacar; Barbara Deracinois; Christophe Flahaut; Rozenn Ravallec; Benoit Cudennec; Guillaume Brisson; Alain Doyen (Food Chemistry, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Thermal treatment of sewage sludge: Impact of the sludge type and origin on the formation of recalcitrant compounds - Sylvain Faixo; Jean-Christophe Garrigues; Mathieu Haddad; Sofiane Mazeghrane; Gilberte Gaval; Florence Benoit-Marquié; Etienne Paul (Water Research, 2025)

Comparison of whole genome sequencing typing tools for the typing of Belgian Legionella pneumophila outbreaks isolates - Fedoua Echahidi; Subin Park; Alaeddine Meghraoui; Florence Crombé; Oriane Soetens; Denis Piérard; Benoit Prevost; Ingrid Wybo; Charlotte Michel (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Acyclovir treatment of varicella-zoster virus meningeal infections and acute kidney injury: a multicentre case series study - Myriam Contamine; Florence Ader; Quentin Lepiller; Benoit Martha; Joséphine Cagnon-Chapalain; Paul Leturnier; Emilie Frober; Kevin Bouiller; Christine Binquet; Christelle Auvray; Lionel Piroth; Mathieu Blot (Infectious Diseases, 2024)

Study of humic-like substances of dissolved organic matter using size exclusion chromatography and chemometrics - Sylvain Faixo; Romain Capdeville; Sofiane Mazeghrane; Mathieu Haddad; Gilberte Gaval; Etienne Paul; Florence Benoit-Marquié; Jean-Christophe Garrigues (Journal of Environmental Management, 2024)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Observation of the Coastal Areas, Estuaries and Deltas from Space - Benoit Laignel; Stefano Vignudelli; Rafael Almar; Mélanie Becker; Abderrahim Bentamy; Jérôme Benveniste; Florence Birol; Frédéric Frappart; Deborah Idier; Edward Salameh; Marcello Passaro; Melisa Menende; et al. (Surveys in Geophysics, 2023)
Coastal regions (including estuaries and deltas) are very complex environments with diverse hydrodynamic and bio-geomorphological contexts and with important socio-economic and ecological problems. These systems are among the most affected by human impact through urbanization and port activities, industrial and tourism activities. They are directly affected by the impact of climate change on sea level, storm surges frequency and strength, as well as recurrence of coastal river floods. A sustainable future for coastal zones depends on our capacity to implement systematic monitoring with focus on: (1) forcings affecting coastal zones at different spatio-temporal scales (sea level rise, winds and waves, offshore and coastal currents, tides, storm surges, river runoff in estuaries and deltas, sediment supply and transport, vertical land motions and land use); (2) morphological response (e.g., shoreline migration, topographical changes). Over the last decades, remote sensing observations have contributed to major advances in our understanding of coastal dynamics. This paper provides an overview of these major advances to measure the main physical parameters for monitoring the coastal, estuarine and delta environments and their evolution, such as the water level and hydrodynamics near the shoreline, water/sediment contact (i.e., shoreline), shoreline position, topography, bathymetry, vertical land motion, bio-physical characteristics of sediments, water content, suspended sediment, vegetation, and land use and land cover.

Risk of major congenital malformation following maternal use of oral fluconazole during the first trimester of pregnancy: a systematic review and meta-analysis - Mathilde Latour; Catherine Vauzelle; Agnès Dechartres; Florence Tubach; Elisabeth Elefant; Benoit Marin (Neurotoxicology and Teratology, 2023)

A short and simple bedside test to detect cognitive fluctuations in patients with dementia with Lewy bodies - Kurt Segers; Florence Benoit; Francisco de Assis Oliveira Rocha; Jean-P. Praet; Murielle Surquin (Acta Neurologica Belgica, 2023)

Data quality control considerations in multivariate environmental monitoring: experience of the French coastal network SOMLIT - Elsa Breton; Nicolas Savoye; Peggy Rimmelin-Maury; Benoit Sautour; Eric Goberville; Arnaud Lheureux; Thierry Cariou; Sophie Ferreira; Hélène Agogué; Samir Alliouane; Fabien Aubert; Sébastien Aubin; et al. (Frontiers in Marine Science, 2023)
Introduction While crucial to ensuring the production of accurate and high-quality data—and to avoid erroneous conclusions—data quality control (QC) in environmental monitoring datasets is still poorly documented. Methods With a focus on annual inter-laboratory comparison (ILC) exercises performed in the context of the French coastal monitoring SOMLIT network, we share here a pragmatic approach to QC, which allows the calculation of systematic and random errors, measurement uncertainty, and individual performance. After an overview of the different QC actions applied to fulfill requirements for quality and competence, we report equipment, accommodation, design of the ILC exercises, and statistical methodology specially adapted to small environmental networks (<20 laboratories) and multivariate datasets. Finally, the expanded uncertainty of measurement for 20 environmental variables routinely measured by SOMLIT from discrete sampling—including Essential Ocean Variables—is provided. Results, Discussion, Conclusion The examination of the temporal variations (2001–2021) in the repeatability, reproducibility, and trueness of the SOMLIT network over time confirms the essential role of ILC exercises as a tool for the continuous improvement of data quality in environmental monitoring datasets.

Improving the accuracy of genomic predictions in an outcrossing species with hybrid cultivars between heterozygote parents: a case study of oil palm (Elaeis guineensis Jacq.) - Achille Nyouma; Joseph Martin Bell; Florence Jacob; Virginie Riou; Aurore Manez; Virginie Pomiès; Hubert Domonhedo; Deni Arifiyanto; Benoit Cochard; Tristan Durand-Gasselin; David Cros (Molecular Genetics and Genomics, 2022)

Silica-clay nanocomposites for the removal of antibiotics in the water usage cycle - Clément Levard; Karima Hamdi-Alaoui; Isabelle Baudin; Amélie Guillon; Daniel Borschneck; Andrea Campos; Mohamed Bizi; Florence Benoit; Corinne Chaneac; Jérôme Labille (Environmental Science and Pollution Research, 2021)

Dementia with Lewy bodies in first-generation immigrants in a European memory clinic - Kurt Segers; Florence Benoit; Jean-Marie Meyts; Gérald Glibert; Sophie Levy; Murielle Surquin (Acta Neurologica Belgica, 2021)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Improving sea level simulation in Mediterranean regional climate models - Fanny Adloff; Gabriel Jordà; Samuel Somot; Florence Sevault; Thomas Arsouze; Benoit Meyssignac; Laurent Li; Serge Planton (Climate Dynamics, 2018)

Influence of bottom trawling on sediment resuspension in the ‘Grande-Vasière’ area (Bay of Biscay, France) - Baptiste Mengual; Florence Cayocca; Pierre Le Hir; Robin Draye; Pascal Laffargue; Benoit Vincent; Thierry Garlan (Ocean Dynamics, 2016)

Estimating Drainage Periods for Agricultural Fields from Measured Data: Data‐Mining Methodology and a Case Study (La JailliÈRe, France) - Aneta Trajanov; Vladimir Kuzmanovski; Florence Leprince; Benoit Real; Alain Dutertre; Julie Maillet‐Mezeray; Sašo Džeroski; Marko Debeljak (Irrigation and Drainage, 2015)
The identification of intensive drainage periods is important for determining mitigation strategies for protecting water against pollution with plant protection products (PPPs). Most attempts to estimate the start, duration and the end of a drainage period are based either on mechanistic modelling approaches or on empirical knowledge about tile drainage. Mechanistic modelling requires many parameters, while the empirical approach does not allow for making the simulations and predictions needed for proposing reliable mitigation measures. In order to complement these two approaches, we have used a data‐mining approach on data from 25 (1987–2011) agricultural seasons (campaigns) from the experimental station La Jaillière, France. The models for estimating the start and the end of the intensive drainage period for a particular campaign have the form of decision trees and tell us which factors influence these dates the most. The start of a drainage period depends mostly on the cumulative drainage and the cumulative rainfall since the beginning of the campaign and the average air temperature of the last 7 days. For estimating the end of a drainage period, the most important variables are the cumulative rainfall of the last 7 days and the average air temperature of the following 7 days. Copyright © 2015 John Wiley & Sons, Ltd.

Pioneers in migration, pioneering in dementia: first generation immigrants in a European metropolitan memory clinic - Kurt Segers; Florence Benoit; Cathérine Colson; Valérie Kovac; Delphine Nury; Valérie Vanderaspoilden (Acta Neurologica Belgica, 2013)

Pelagic food web patterns: do they modulate virus and nanoflagellate effects on picoplankton during the phytoplankton spring bloom? - Pascaline Ory; Hans J. Hartmann; Florence Jude; Christine Dupuy; Yolanda Del Amo; Philippe Catala; Françoise Mornet; Valérie Huet; Benoit Jan; Dorothée Vincent; Benoit Sautour; Hélène Montanié (Environmental Microbiology, 2010)
Summary As agents of mortality, viruses and nanoflagellates impact on picoplankton populations. We examined the differences in interactions between these compartments in two French Atlantic bays. Microbes, considered here as central actors of the planktonic food web, were first monitored seasonally in Arcachon (2005) and Marennes‐Oléron (2006) bays. Their dynamics were evaluated to categorize trophic periods using the models of Legendre and Rassoulzadegan as a reference framework. Microbial interactions were then compared through 48 h batch culture experiments performed during the phytoplankton spring bloom, identified as herbivorous in Marennes and multivorous in Arcachon. Marennes was spatially homogeneous compared with Arcachon. The former was potentially more productive, featuring a large number of heterotrophic pathways, while autotrophic mechanisms dominated in Arcachon. A link was found between viruses and phytoplankton in Marennes, suggesting a role of virus in the regulation of autotroph biomass. Moreover, the virus–bacteria relation was weaker in Marennes, with a bacterial lysis potential of 2.6% compared with 39% in Arcachon. The batch experiments (based on size‐fractionation and viral enrichment) revealed different microbial interactions that corresponded to the spring‐bloom trophic interactions in each bay. In Arcachon, where there is a multivorous web, flagellate predation and viral lysis acted in an opposite way on picophytoplankton. When together they both reduced viral production. Conversely, in Marennes (herbivorous web), flagellates and viruses together increased viral production. Differences in the composition of the bacterial community composition explained the combined flagellate‐virus effects on viral production in the two bays.

Evaluation of quantitative and qualitative aspects of mitochondrial function in human skeletal and cardiac muscles - N'Guessan Benoit; Joffrey Zoll; Florence Ribera; Elodie Ponsot; Eliane Lampert; Renée Ventura-Clapier; Vladimir Veksler; Bertrand Mettauer (Molecular and Cellular Biochemistry, 2004)

Apolipoprotein A-I(R151C)Paris is defective in activation of lecithin:cholesterol acyltransferase but not in initial lipid binding, formation of reconstituted lipoproteins, or promotion of cholesterol efflux - Ulrike Daum; Claus Langer; Nicolas Duverger; Florence Emmanuel; Patrick Benoit; Patrice Patrice Denèfle; Ali Chirazi; Paul Cullen; P. Haydn Pritchard; Eric Bruckert; Gerd Assmann; Arnold von Eckardstein (Journal of Molecular Medicine, 1999)